Clinical profile of adults with Guillain Barre Syndrome in North-West Rajasthan, India - Vyas, Arvind; Jaiswal, Kartik; Swami, Sarika; Rankawat, Madhu Sudan (International Journal of Advances in Medicine, 2016)
Background: Guillain Barre Syndrome is a heterogenous symptom complex and an important cause of acute flaccid paralysis in children as well as adults. This study was conducted to see the clinical profile of adults admitted with Guillain Barre Syndrome. Methods: This prospective study was conducted in the department of medicine and neurology of S. P. Medical College and A.G. Hospitals, Bikaner, Rajasthan, India. Clinical diagnosis of Guillain Barre Syndrome was based on proposed criteria. Clinical data of 30 such patients were analysed. Results: In this part of India, Guillain Barre Syndrome is common in early decades and second peak is seen in 4th decade. Male to female ratio was 3.28:1. 70% patients were from rural area. Maximum number of cases came in month of May followed by April, March, July, 23.33%, 16.66%, 13.33%, 13.33% respectively. No patient came in January and October. Preceeding illness was present in 73.3% of cases. Neurological examination showed that 63.33% cases presented with quadriparesis, 50% had cranial nerve involvement, 36.6% cases had paraparesis only, 36.6% had autonomic instability. Conclusions: In this part of Rajasthan, Guillain Barre Syndrome has bimodal occurrence with male preponderance. Commoner in rural population. March to July found common months of occurrence of disease. Most patients have antecedent illness and quadriparesis is commonest presentation.